How do reviews from professional critics interact with other signals of product quality? Evidence from the video game industry†. Issue 6 (2nd November 2015) - Cox, Joe; Kaimann, Daniel
Abstract: Experience goods are characterised by information asymmetry and a lack of ex ante knowledge of product quality, such that reliable external signals of quality are likely to be highly valued. Two potentially credible sources of such information are reviews from professional critics and 'word of mouth' from other consumers. This paper makes a direct comparison between the relative influences and interactions of reviews from both of these sources on the sales performance of video game software. In order to empirically estimate and separate the effects of the two signals, we analyze a sample of 1480 video games and their sales figures between 2004 and 2010. We find evidence to suggest that even after taking steps to control for endogeneity, reviews from professional critics have a significantly positive influence on sales which outweighs that from consumer reviews. We also find evidence to suggest that reviews from professional critics also interact significantly with other signals of product quality. Consequently, we contend that professional critics adopt the role of an influencer, whereas word‐of‐mouth opinion acts more as a predictor of sales in the market for video games. Copyright © 2015 John Wiley & Sons, Ltd.